Distribution of the subgenus Psyllophora (Degl.) Peterm. (Carex L.) in Ukraine - Sosnovska, Svitlana; Danylyk, Ivan; Serednytska, Svitlana (Biodiversity: Research and Conservation, 2013)
It has been established that species of the subgenus Psyllophora (Degl.) Peterm. (Carex L.) are characterized by very disjunctive areas and the limited regional distribution (Carex pauciflora Lightf. and C. rupestris All.), or are known from a few localities only (C. obtusata Liljebl.). Dioecious species of this subgenus (C. dioica L. and C. davalliana Smith), reach the eastern and southern limits of their distribution in Ukraine, where they are the most widespread. However, a big number of their localities have been already lost.